Heard Utopia vs Utopian Hearing: Haas's in vain and Political Ambivalence in New Music. Issue 1 (26th April 2018) - SILVA, MAX
Abstract: This article examines Haas's politically programmatic work in vain in relation to a later essay wherein Haas disavows politically motivated composition. The first section investigates Haas's allegation that in vain 's ideological failure is due to its politically inappropriate semantic richness. Yet multiple interpretive passes through the piece show that in vain fails to be ideologically straightforward only because of a deeper ethical commitment to an aesthetics of defamiliarization. In the second section, I show how the basic political narrative is complicated by the estranging effect of darkness; in the third section, I align Haas's aesthetics with a post-Spectral ethics, and consider how the narrative meaning of overtone chords is complicated by their potential for challenging preconceived categories of listening. The final section returns to the essay and its blind spot for this deeper ethical aesthetics that obscures in vain 's ideological clarity, speculating that Haas's omission betrays hidden anxieties about the modernist ethical project.